Chapter 11 Understanding the Social Care Crisis in England Through Older People's Lived Experiences - Ward, Lizzie (Springer Nature, 2020)
The chapter's focus is social care in England where responsibility for the organisation and funding of care has shifted from the state to the individual. It draws on a qualitative research project about the experiences of older people who are paying for their social care